EVALUATION OF ANTIBACTERIAL ACTIVITY OF DIFFERENT SOLVENT EXTRACTS OF CICHORIUM INTYBUS (L.) GROWING WILD IN EAST PART OF KOSOVO - F. Faiku; A. Haziri; I. Mehmeti; D. Bajrami; I. Haziri (Journal of Animal and Plant Sciences, 2016)
Now is known that organic extracts of medicinal plants can be used as antibacterial agents. Effectiveness of extract on bacterial growth depends sort of medicinal plant. In this research we used a medicinal plant Cichorium intybus (L.) which was grown wild in Kosovo and was used for a long time against bacterial infections. Antibacterial efficiency of Cichorium intybus (L.) were examined using methanol, ethyl acetate, acetone, diethyl ether, water and chloroform extracts and tested against three Gram positive bacteria Staphylococcus aureus (food isolate), Staphylococcus aurous (clinical isolate), Listeria monocytogenes (clinical isolate)Gram negative bacteria Escherichia coli (clinical isolate). The antibacterial activity was determined by using agar disc diffusion method. The zones of inhibition from extracts were compared to that of penicillin G as standard.  More pronounced activity was shown by water and ethyl acetate extracts of the Cichorium intybus (L.). The ethyl acetate extract showed antibacterial activity against Staphylococcus aureus. Aqueous extract of the plant with concentration 5 mg/ml showed a stronger antibacterial activity against bacteria Eshcheria coli. Also aqueous extracts of the Cichorium intybus (L.) showed a stronger antibacterial activity as penicillin G against bacteria Staphylococcus aureus. The antibacterial activity of the Cichorium intybus (L.) was due to the presence of various secondary metabolites such as phenols and flavonoids . Hence, this plant can be used to discover bioactive natural products that may serve as leads in the development of new pharmaceuticals.
Keywords: Cichorium intybus (L.); antibacterial activity; agar disk diffusion method; organic extracts